The Relationship HUBUNGAN ASUPAN LEMAK, ASUPAN GARAM DAN STATUS GIZI DENGAN TEKANAN DARAH PENDERITA HIPERTENSI DI UPT. PUSKESMAS SINGKAWANG TIMUR I - Haska, Yulia Farahdini (JURNAL BORNEO AKCAYA, 2020)
Hypertension is often called a silent killer. This study aimed to analyse the relationship of fat intake, salt intake and nutritional status with the blood pressure of people with hypertension in UPT. Puskesmas Singkawang Timur I. The data were collected by accidental sampling with data measuring instruments by using a questionnaire and food recall’s form. The results of the bivariate analysis showed that the respondents with high fat intake had high blood pressure were 57 people (78.1%); the respondents with low salt intake had high blood pressure were 33 people (54.8%); the respondents with normal nutritional status had high blood pressure were 56 people (76.72%), and the respondents with nutritional status obesity had high blood pressure were 17 people (23.28%). The research found out that there was not any correlation between fat intake and blood pressure; and between nutritional status and hypertensive patient’s blood pressure. But, there was a positive correlation between salt intake and blood pressure in the UPT. Puskesmas Singkawang Timur I. Keywords: Fat, Salt, Hypertension